A novel in vivo method to detect DNA sequence variation. - Faham, M; Cox, D R (Genome Research, 1995)
Mismatch repair detection (MRD) is an in vivo method that uses a change in bacterial colony color to detect DNA sequence variation. DNA fragments to be screened for variation are cloned into two MRD plasmids, and bacteria are transformed with heteroduplexes of these constructs. The resulting colonies are blue in the absence of a mismatch and white in the presence of a mismatch. MRD is capable of detecting a single mismatch in a DNA fragment as large as 10 kb in size. In addition, MRD has the potential for analyzing many fragments simultaneously, offering a powerful method for high-throughput genotyping and mutation detection in a large genomic region.